THE IMPACT OF GLOBALIZATION ON THE ENGLISH LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
his article explores the multifaceted relationship between globalization and the English language, examining how economic, cultural, and technological integration has transformed English from a national tongue into a global lingua franca. The study investigates the emergence of "World Englishes" and the linguistic shifts triggered by digital communication. By analyzing current trends, the research highlights the tension between linguistic homogenization and the localized adaptation of English. The findings suggest that while globalization solidifies English as the primary medium for international discourse, it simultaneously fosters a pluralistic evolution of the language, leading to new grammatical and lexical structures.